Hubungan antara Kepemimpinan Digital dan Sumber Daya Manusia dengan Daya Saing UMKM di Kabupaten Pandeglang - Popy Mayangsari; Munawaroh Munawaroh (Journal of Management and Creative Business, 2025)
In this study, attention is focused on exploring the relationship between the competitiveness of MSMEs in Pandeglang Regency and digital leadership and human resources. The quantitative method is used to collect survey data and distribute it to MSME actors who meet certain requirements. Pearson correlation test is used to assess the relationship between variables in data analysis. This study proves that there is a strong relationship between digital leadership and the competitiveness of MSMEs based on a correlation value of 0.606. Furthermore, a correlation value of 0.748 indicates a significant relationship between human resources and the competitiveness of MSMEs. The simultaneous relationship between digital leadership and human resources and the competitiveness of MSMEs shows a correlation value of 0.751 which indicates a significant contribution.